Pengaruh Penerapan Model Open-Ended PBL Terhadap Kemampuan Berpikir Kreatif Matematika Peserta Didik - Safaria, Sri Anandari; Patih, Tandri; Arifa, Nur (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The ability to think creatively is one of the important skills that needs to be developed in learning mathematics. This research aims to see that the Open-Ended Problem Based Learning (Open-Ended PBL) model can help improve students' creative mathematical thinking abilities. Using a quasi-experimental approach, research was conducted on class VII students at one of the state junior high schools in Central Buton Regency. Two classes were chosen randomly, namely one as an experimental group, namely class VII-B, which received learning using the Open-Ended PBL model, and the other as a control group, namely class VII-A, with conventional learning. After the learning process, students' creative thinking abilities are analyzed using statistical tests, starting with normality and homogeneity tests as well as the independent sample t-test. The results show that students taught with the Open-Ended PBL model experienced significant improvement, with an average N-gain of 0.42 and a significance value of 0.00. A p-value of less than 0.05 is evidence that the application of the Open-Ended PBL model has a significant influence on increasing students' creative mathematical thinking abilities. These findings show that the Open-Ended PBL approach not only helps students understand mathematics more deeply, but also encourages them to think more openly and creatively. This model can be a strategic choice for teachers in creating more meaningful mathematics learning.